Effect of initial pressure of oblique-blowing airflow and folding-in airflow on yarn tucked-in in the pneumatic tucked-in selvedge apparatus. Issue 21 (November 2021) - Liu, Yisheng; Zhou, Xinlei; Cheng, Xiaoying; Liu, Dandan
In this paper, numerical simulation and laboratory experiments were combined to research the tucked-in behavior of the yarn in the pneumatic tucked-in selvedge apparatus, and explore the effect of initial pressure of oblique-blowing airflow and folding-in airflow on yarn tucked-in. This work focused on the motion of a single yarn of which one end was fixed while the other was free. Initial pressures for oblique-blowing airflow and folding-in airflow were set as parameters. A numerical model was developed to simulate the process based on the one-way fluid–structure interaction. Then a laboratory experiment was carried out with the help of a high-speed camera to record the motion behaviors of yarns. The motions were compared with the simulation data and showed that the proposed numerical model can properly replicate the motion of yarn and its points in the airflow field. Each group of yarns with different initial pressures was able to be tucked-in and had an elongation. Increasing the initial pressures of oblique-blowing airflow from 0.3 MPa to 0.4 MPa and folding-in airflow from 0.35 MPa to 0.4MPa shortened the time for the yarn to complete the entire oblique-blowing and tucked-in process by 0.4625 ms, and extended the yarn elongation by 0.151 mm.